Internet and Social Media Use Among Patients with Hair and Scalp Disorders: A Behavioral Analysis - Coulanges, Edwine; Olagun-Samuel, Christine; Thomas, Jamon; Adotama, Prince (Dermatology Practical & Conceptual, 2026)
Introduction: TikTok, a social media platform, is a tool for disseminating dermatological public health education. On TikTok, like other social media platforms, both board-certified dermatologists and non-medical providers (“influencers”) provide dermatological advice, but how the quality of the advice compares between the two creator groups is unclear.Objectives: This study sought to assess similarities and differences in the language used within content, user receptibility, and engagement and the utility of online education in understanding hair and scalp disorders.Methods: A cross-sectional analysis of 97 TikTok videos from 2023 was performed to evaluate the content quality of videos made by dermatologists and influencers regarding three common hair and scalp disorders: seborrheic dermatitis, telogen effluvium, and traction alopecia.Results: Dermatologists and influencers had similar user engagement, but 49% of dermatologists were more likely to recommend standard treatments compared to 27% of influencers; 46% of influencers were more likely to recommend alternative treatment options compared to 25% of dermatologists. An analysis of user comments to assess audience understanding indicated that the three disorders were often confused with at least 2–3 other similar hair and scalp conditions.Conclusions: This study highlights a need to clarify for patients the standard of care for common hair and scalp disorders. This study also identified a universal lack of messaging encouraging users to seek in-person medical attention for their dermatological concerns.